ChemInform Abstract: Nickel‐Rich Layered Lithium Transition‐Metal Oxide for High‐Energy Lithium‐Ion Batteries. Issue 26 (June 2015) - Liu, Wen; Oh, Pilgun; Liu, Xien; Lee, Min‐Joon; Cho, Woongrae; Chae, Sujong; Kim, Youngsik; Cho, Jaephil
Abstract Review: [structure, cathode material performance enhancement, solid electrolyte interface engineering, safety; 89 refs.